Televizyon reklamcılığı ve Türkiye’de toplumsal etkileri - Şip, Funda (My University, 1999)
Individuals living in a consumption community have been estranged themselves, they have been unsatifactorily aimless and as a result, they spiritually have got tired under the conditions in which the life was in service of consumption rather than it was of life, it was excessively attached importance on consumption, all the things which were tangible and intangible have been materialized and consumed, excessively consumption has been identified with social success and statue. Although advertisement solely could not form a consumption society, it is a sector that acts as an accelerator for that process. Advertisements that bring cultural standardization lead several social-economic, psychological and social costs, at the same time they cause that consumption placed in capitalist societies as a life style. In less developed countries, consumption was attempted to be increased by trying to exceed western life patterns with global advertisements. Most of them surrendered themselves to global standards of the world and left their traditional values. After the 1980 's. advertisements that also affected Turkish society were in a transition from contented society to consuming society by adopting the values particular to western consuming patterns and consumption society. A resistance method must be improved in order to survive our brains which are the victims of the messages struggled to take over a permanent place in minds between an intensive competition and unilateral communication between producer and consumer (passive consumer, active producer). Advertisement was characterized to hoodwink more by improving technology and visual activity of TV. Consumer behaviors, social-cultural and driven factors were also tried to be solved. Emotional motives play a more selective role than rational ones in the purchasing decision of consumers. Convictions, beliefs and behaviors can be changed by persuasion, furthermore the advertisements in which the method of persuasion were not used also have affects on consumers. A few numbers of consumers decide to purchase products by considering the physical characteristics of them. Consumer selects only the products that are harmonious with their life styles and their self-respects as a result of their selective perception. In an advertisement, because of the fact that using uncertain expressions, entirely giving missing and true information lead consumers to purchase the products which they do not need, it is necessary to use those factors carefully to clarify and protect them. Advertisement manipulates consumers with its one-sided attitude instead of giving such information. As a result of the fact that the aesthetic and cultural standards were negatively used and the popular ones not the required ones were supported in advertisements, they became a power that removes standards. It was not reached successful results for the Law of Honest Applications in Advertisingin which the responsibilities of the parties related with advertising were stated although all the studies on it. A declared low about the protection of consumer numbered 4077 in 8th September 1995 prohibits advertisements and notices which are against the rules of Common Morals, Truth and Honesty. Brands have been gained characteristics over-national and over-beliefs. A brand image, which is formed by combining the emotional impressions from the symbolic and rational meaning of it, creates a brand character. When an advertisement with improperly exaggerated, colorful, vigorous visions are addressed to Utopias, the product become enormous in the eyes of consumers However in the usage stage the real characteristics of product would be revealed. If man and woman think that they can overcome their individual insufficiencies according to what issues created for them in advertisements, they are easily persuaded and they purchase the products. Sexuality of woman is exploited and easily placed on commercial fantasies. Family factor is specially used for durable consumer goods and foodstuffs. The influence of the advertising sector to formation of ideas, expectations, and life styles of the social foundations increased the giving importance of social and moral responsibility in preparing of advertisements. If we think that the advertisement is a system issue, it undertakes the most important roles in the formation of life styles and standards. While it plays this role, like proved in entire thesis, advertisement does not deprived of manipulate influence to consumer in any ways, it makes consumers passive. First step to lower the destructive influences of advertisement to minimum level and to train healthy individuals for the society is that all the workers in advertising sector must behave respectfully to society conscience, try to reach high values, and consumers must be more conscious to protect themselves against the manipulative influence of advertisement.
Keywords: REKLAMCILIK-REKLAM FİLMLERİ; TELEVİZYON REKLAMCILIĞI